'Transit Faithfuls' or 'Transit Leavers'? Understanding mobility trajectories of new parents. (June 2019) - McCarthy, Laura; Delbosc, Alexa; Currie, Graham; Molloy, Andrew
Abstract: First-time parenthood is typically associated with an increase in car orientated travel behaviour. As cities face increasing pressure to reduce growing levels of private car use, understanding the ways in which to prevent the adoption of car-based mobility during this period is becoming increasingly important. However, while much is known about aggregate changes in travel behaviour following parenthood, less is understood about differences that may exist at the individual level. Understanding these differences will help planners and policymakers to introduce more targeted policy interventions for new parents, assisting to curb the tendency towards car orientation. A latent class analysis is conducted using data from a survey of new parents in Melbourne, Australia. The results reveal five distinct mobility patterns following parenthood. These range from a marked decline in public transit use – Transit Leavers – through to remarkably consistent travel behaviour prior to and following parenthood – Transit Faithfuls . The findings show that not all parents adopt car orientated travel behaviour following parenthood. Caregiving and employment status, as well as car ownership changes, are shown to be crucial in determining the extent to which travel behaviour changes and new car orientated travel behaviour is adopted. Moreover, each group display distinct characteristics and constraints on their travel choices. This suggests targeted interventions specific to individual groups are necessary to curb the tendency towards car-based mobility among new parents. Highlights: A latent class analysis reveals five distinct changes in mobility patterns among new parents. These range from remarkably consistent travel prior and following parenthood to a marked decline in public transit use. Not all new parents adopted car orientated travel behaviour following parenthood, for a minority their car use declined. Caregiving and employment status are crucial in determining the extent to which travel behaviour changes. As each group displays different travel constraints, targeted interventions specific to individual groups are proposed.